2008
DOI: 10.1371/journal.pmed.0050045
|View full text |Cite
|
Sign up to set email alerts
|

Initial Severity and Antidepressant Benefits: A Meta-Analysis of Data Submitted to the Food and Drug Administration

Abstract: BackgroundMeta-analyses of antidepressant medications have reported only modest benefits over placebo treatment, and when unpublished trial data are included, the benefit falls below accepted criteria for clinical significance. Yet, the efficacy of the antidepressants may also depend on the severity of initial depression scores. The purpose of this analysis is to establish the relation of baseline severity and antidepressant efficacy using a relevant dataset of published and unpublished clinical trials.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

63
1,424
11
69

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,094 publications
(1,567 citation statements)
references
References 28 publications
63
1,424
11
69
Order By: Relevance
“…Kirsch et al (2008) present suggestive, though not conclusive, evidence that certain commonly prescribed antidepressants may only be effective for those with severe, rather than moderate, depression at study baseline. With this in mind, it may be advantageous to incorporate the following preplanned interim analysis in one's trial of the new antidepressant: if it is observed that the treatment effect is sufficiently low among those with moderate baseline depression, one will enroll only those with severe baseline depression for the rest of the trial.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Kirsch et al (2008) present suggestive, though not conclusive, evidence that certain commonly prescribed antidepressants may only be effective for those with severe, rather than moderate, depression at study baseline. With this in mind, it may be advantageous to incorporate the following preplanned interim analysis in one's trial of the new antidepressant: if it is observed that the treatment effect is sufficiently low among those with moderate baseline depression, one will enroll only those with severe baseline depression for the rest of the trial.…”
Section: Introductionmentioning
confidence: 66%
“…As described above, Kirsch et al (2008) present suggestive, but not conclusive, evidence from a meta-analysis that a class of commonly used antidepressants may not be superior to placebo for those with moderate pretreatment depression, while they are superior to placebo for those with severe pretreatment depression. We consider a method for designing a trial of a hypothetical new antidepressant with this in mind.…”
Section: ·1 Overviewmentioning
confidence: 77%
See 2 more Smart Citations
“…A meta-analysis has shown that SSRIs are less effective in paediatric than adult MDD, with minimal gains after four weeks of treatment (24). It is generally believed that the antidepressant efficacy of SSRIs increases as a function of baseline depression severity, but it is also hypothesised that this may be due to decreased responsiveness to the placebo effect of SSRIs, rather than to increased responsiveness to medication (25). It is notable that previously published data that supported the efficacy and safety of SSRIs in paediatric populations has shown to be incorrect when reanalysed (26).…”
Section: Introductionmentioning
confidence: 99%